2008
DOI: 10.1007/s10600-009-9194-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of amino-acid derivatives of chrysin

Abstract: Various conjugates of amino acids with chrysin in which the amino acid was bonded through the C-or N-terminus to the flavone were prepared using peptide chemistry methods (symmetric anhydrides and activated esters).Flavonoids are the most widely distributed compounds of natural origin. They can be found in practically all plant species. At present, flavonoids comprise about 6500 natural compounds [1]. The study of flavonoids is becoming increasingly interesting because of the important role that they play in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 34 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…In chrysin C-5-hydroxyl group is relatively less reactive than C-7-OH due to steric effect and strong intra-molecular H-bonding between C-5-OH and the carbonyl oxygen (at C-4) [33]. Thus, C-7-hydroxyl group of chrysin was selectively reacted with dibromoalkane (1,2; 1,3 and 1,4) to obtain corresponding C-7-O-bromoalkyl chrysin as intermediates 1a-1c (Scheme-I).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In chrysin C-5-hydroxyl group is relatively less reactive than C-7-OH due to steric effect and strong intra-molecular H-bonding between C-5-OH and the carbonyl oxygen (at C-4) [33]. Thus, C-7-hydroxyl group of chrysin was selectively reacted with dibromoalkane (1,2; 1,3 and 1,4) to obtain corresponding C-7-O-bromoalkyl chrysin as intermediates 1a-1c (Scheme-I).…”
Section: Resultsmentioning
confidence: 99%
“…The encouraging biological profiles of the flavonoids particularly of chrysin and in continuation of our current research interests [32] on searching and development of antimicrobial agent from natural resources led us to extend our work towards the synthesis of some new chrysin derivatives and their biological evaluations. In connection to this, it was anticipated that amines and triazole derivatives of chrysin may exhibit significant antimicrobial activity compared to the other derivatives so far reported in the literature [13,15,[33][34][35]. Therefore, 18 different derivatives (Fig.…”
Section: Introductionmentioning
confidence: 94%
“…It is reported that most of the absorbed chrysin was detectable as glucuronic acid and sulfate acid conjugates with the unprotected hydroxyl at 5-and 7-positions of chrysin in the blood and vascular system [14,15]. In order to obtain more pharmacologically active and more selective drugs with less adverse reactions for clinical use, a large number of studies have been performed via the synthesis of chrysin derivatives [16][17][18][19][20].Carbohydrates are ubiquitous in nature and play a key role in a number of important biological processes, including fertilization, cell-cell recognition, immune response, hormone regulation, and inflammation. Sugar appendages add important features to the shape and the stereoelectronic properties of a molecule and thus wield remarkable influences.…”
mentioning
confidence: 99%
“…The furocoumarin hydrazones 9-12 were obtained by treating alcohol solutions of the respective thiones 5-8 with hydrazine hydrate [8,9] (Schemes 1-4).…”
mentioning
confidence: 99%